MEMBANGUN SISWA SADAR LINGKUNGAN MELALUI INTEGRASI PENDIDIKAN LINGKUNGAN HIDUP KE DALAM PEMBELAJARAN IPA DI SDN 1TEGALDLIMO SEBAGAI ALTERNATIF MEWUJUDKAN SEKOLAH BERSIH DAN HIJAU - Dwi Andriani, Zulfi Jumala (Indonesian Journal of Science Learning (IJSL), 2023)
Efforts to instill the formation of students in preserving the environment through environmental education into the formal learning process in schools. Environmental education is a field of science that must be studied as early as possible in various educational institutions, including at the State Elementary School 1 Tegaldlimo, by integrating environmental science into other disciplines. The link or interdependence between biological environmental education and other sciences, especially with social studies lessons at the school level of SDN 1 Tegaldlimo, is another way to introduce environmental struggles to students. The purpose of this research is to integrate environmental education into social studies learning at the State Elementary School 1 Tegaldlimo in order to create environmentally conscious students. This type of research uses qualitative methods. The findings of the study found that environmental education could be integrated into social studies learning at SDN 1 Tegaldlimo through several basic competency criteria. Environmental education is a discourse on student awareness of the school environment, enlightenment of students on the school environment, as well as many benefits for life in order to realize a clean and green school. A green school is a school that has a positive policy in environmental education, biology, is in all aspects of activities taking into account environmental aspects. A green and clean school where at SDN 1 Tegaldlimo had instilled an attitude in its students to instill the values ​​of the biological environment by using the school environment as the origin of learning. From what will happen, green school research aims to foster constructive behavior and behavior in students, teachers and school principals against environmental struggles in the school and its surroundings. students are taught how to plant trees around the school by using the school as a learning resource. Then the activities of these students will create a green and hygienic school that cares about the environment.